Thomas Cranmer's Doctrine of the Eucharist - Newman Brooks, Peter. author. aut Link
XXVII, 195 p.
Keywords: '...essential reading for all students of the English Church.' Patrick Collinson Thomas Cranmer (1489-1556) is arguably the most controversial figure of the English Reformation. The sixteenth century was a period of fierce theological controversy and no doctrine concerned contemporaries more than the vexed issue of the Eucharist. Scholars have always found it notoriously difficult to determine Cranmer's conviction on this central matter of the Christian faith. This and many other questions that have long troubled Cranmer scholars receive fair and full treatment in this absorbing study. This book re-establishes itself as the definitive exposition of Cranmer's doctrine of the Eucharist.